Rethinking: Women's Political Rights, Digital Safety, and Election - Lian Agustina Setiyaningsih; Muhammad Hanif Fahmi; Sekar Arum Nuswantari; Sri Widayati; Priyo Dari Molyo (Journal of Transformative Governance and Social Justice, 2023)
The position of equality in political rights is still being studied seriously and is full of pros and cons in various countries. Straightening the role of women's rights in politics is extensive homework for this nation. Even in today's conditions, the representation of women in the political sphere at the beginning of the struggle was unacceptable to male politicians and the public. The literature review aims to rethink the relationship between women's political rights, digital safety skills, and general elections. All three have a common thread for measuring the existence of women in the political realm. This condition can be seen from the role of women as political actors who run for office, as well as women as owners of voting rights in general elections. Both can be viewed as subjects and objects in general elections to restore the spirit of democracy in Indonesia. The answer to the above problems is establishing digital safety as a digital literacy ecology. The need for this condition refers to women's political struggle to get crucial political affirmation.